No. 6. Volume 6 - Asano, Atsuko, 1954- (No. 6, 2014)
A series of strange incidents cast a pall over No. 6 as it prepares to celebrate its "Holy Day." Meanwhile, in the tunnels beneath the Correctional Facility, Shion and Rat meet with the mysterious "Elder," who reveals the perverse origins of No. 6, and their connection to Rat's past. How will Rat react when Shion begins to touch his most secret scars?